Dispersion of Multidrug Resistant Bacteria and Fecal Bacteria into Field Soils of Japan through Compost Application (Global Journal of Medical Research, 2022)
As huge amount of organic fertilizer of fecal origin has annually been dispersed into field soils without checking included hazardous bacteria. In order to estimate their contamination level in Japanese field soils, MRB and fecal bacteria in nine composts, which had originated from cattle feces, pig feces, and chicken droppings andbeen applied on soils for organic farms in various regions of Japan, were evaluated by using an originally developed analysis method. The tested composts included higher number of general bacteria (from 7.08x109 MNP g-1 dry matter to 316.2x109 MNP g-1), where gram-positive bacterial groups, such as Actinobacteria, Bacillus sp., and Staphylococcus sp., and the other Firmicutes were the numerical dominant in most of them (22% to 98%). Six out of nine composts included over the detection limit of MRB, which proliferated under mixture of 25ppm each of streptomycin, chloramphenicol, and ampicillin(1x104 MPN g-1 dry matter to 84.9x104 MPN g-1), where gram-negative MBR were the numerically dominant(33.3% to 100%). As most of the composts included not only fecal bacteria and pathogenic bacteria but also MRB of fecal origin such as Bacteroides sp., B.coprocola, and Borrelia recurrent, large area of Japanese field soils were suggested to be contaminated with such the fecal bacteria through application of compost.